2021
DOI: 10.1007/jhep01(2021)095
|View full text |Cite
|
Sign up to set email alerts
|

Elastic positivity vs extremal positivity bounds in SMEFT: a case study in transversal electroweak gauge-boson scatterings

Abstract: The positivity bounds, derived from the axiomatic principles of quantum field theory (QFT), constrain the signs of Wilson coefficients and their linear combinations in the Standard Model Effective Field Theory (SMEFT). The precise determination of these bounds, however, can become increasingly difficult as more and more SM modes and oper- ators are taken into account. We study two approaches that aim at obtaining the full set of bounds for a given set of SM fields: 1) the traditional elastic positivity approac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 60 publications
(85 reference statements)
2
64
0
Order By: Relevance
“…In particular, positivity bounds have been used to constrain Standard Model EFT [19][20][21][22][23][24][25][26]. For example, it has been shown that the vast majority of the parameter space of the dimension 8 anomalous quartic gauge couplings is excluded by the positivity bounds [19,20,23,25]. For another example, strong constraints can also be obtained for Horndeski theory when pairing together with cosmological parameter estimation analysis [36].…”
Section: Jhep05(2021)255mentioning
confidence: 99%
“…In particular, positivity bounds have been used to constrain Standard Model EFT [19][20][21][22][23][24][25][26]. For example, it has been shown that the vast majority of the parameter space of the dimension 8 anomalous quartic gauge couplings is excluded by the positivity bounds [19,20,23,25]. For another example, strong constraints can also be obtained for Horndeski theory when pairing together with cosmological parameter estimation analysis [36].…”
Section: Jhep05(2021)255mentioning
confidence: 99%
“…Using the Warsaw basis for the dimension-6 SMEFT [28], and considering the high-energy phase where all particles are massless and the electroweak symmetry unbroken, it is straightforward to check that there are no dimension-6 contributions to the four-fermion positivity bounds at tree level. This differs from the case of 2 → 2 gauge bosons scattering, where non-redundant trilinear couplings enter the bounds at tree-level and strenghthen the bounds on dimension-8 operators [10,11,14].…”
Section: Jhep04(2021)115mentioning
confidence: 86%
“…More generally, every setting where the flavor-blind parameters are degenerate is seen to be compatible with the positivity conditions. Still, the positivity constraints are such as to reduce the full parameter space by a factor of 2 14 .…”
Section: Jhep04(2021)115mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, many dimension-8 operators are subject to positivity bounds arising from fundamental principles of quantum field theory including unitarity and analyticity, see [20][21][22][23][24][25][26][27][28][29] for some recent applications. The LEFT is a valid EFT in its own right, independent of whatever its UV completion may be.…”
Section: Introductionmentioning
confidence: 99%